Horthy kormányzó németországi látogatása 1938 augusztusában - Olasz, Lajos (Közép-Európai Közlemények, 2015)
In summer 1938, Hitler was already preparing to gain control of Czechoslovakia. Hitler expected full co6operation of the Hungarian Government for the sake of re6acquiring Highland annexed in 1920. On 21st August 1938, Regent Horthy, accompanied by several of his ministers, visited Germany, where he was welcomed with high celebration. During the discussions, Hitler made attempts to induce the Hungarian delegation to get involved in the military action against Czechoslovakia. However, Horthy and his ministers rejected it. They referred to the unpreparedness of the Hungarian military forces, the intervention of France and Great Britain, and the unpredictable reactions of the Little Entente states. Hungarian politicians insisted on revision, but preferably they wanted to implement it by by way of negotiations. Consequently, on 22nd August they agreed with the Little Entente states that Hungary was allowed to get armed freely; however, they mutually relinquished to resort to force. The German government was disappointed to find that it could not count on Hungary in its plans.